A comparison of estimated and measured values of solar radiation in Elazig, Turkey - Togrul, IT; Onat, E (Pergamon-Elsevier Science Ltd, 2000)
In this study, variation of global solar radiation reaching the Elazig region at hourly and monthly average daily periods was examined measuring daily global solar radiation between April 1994 and March 1995 by a Kipp-Zonen pyranometer. Taking the measured values as reference, the statistical performance of the three equations used in estimating the monthly average global solar radiation was investigated. Secondly, it was shown that 'bright sunshine hours/daylength' and its standard derivation could be used to estimate the monthly daily 'solar radiation/extraterrestrial radiation' by applying the maximum likelihood quadratic fit method to the data taken from the state Meteorological Office in Elazig between 1983-1994. (C) 1999 Elsevier Science Ltd. All rights reserved.
Keywords: estimation of solar radiation; Kipp-Zonen pyranometer